Determination of heavy metals contamination in the river water of Sungai Maong and enviromental awareness among the villagers of Kampung Sungai Maong - Nurhafizah, Binti Mohd Selihin (Universiti Malaysia Sarawak (UNIMAS), 2012)
ýAnthropogenic activities have given great pressures on the environment including the river and therefore public awareness is important in order to sustain our natural resources. This study was carried out to analyze the heavy metals concentrations of the surface water of four stations within Sg. Maong catchment and also to investigate the environmental awareness of the villagers in Kpg Sg. Maong with regard to solid waste management and recycling. Elemental concentrations of Zn, Fe, Pb, Cu, As and Al were measured using atomic absorption spectroscopy (AAS). The mean values of the heavy metals are; Zn 0.91 mg/L; Fe 0.61 mg/L; Pb 0.018 mg/L; As 0.033 mg/L; Al 1.85 mg/L; whereas Cu was not detected in all water samples. The average trend of heavy metals in Sg. Maong was observed in the order: AI>Zn>Fe>As >Pb. Pearson correlation analysis was done to determine the degree of association between the heavy metals and pH. Fe and As showed high correlation with pH whereas between metals, Zn/Fe, Zn/Al, Fe/As and Fe/Al showed a positive correlation)lt was observed that the surface water of Sg. Maong was not heavily contaminated with Fe, Zn, Al and Cu as these concentrations were below the standard limit of Interim National Water Quality Standard (INWQS). At the same time, a convenience sampling method was conducted in Kpg. Sg. Maong to investigate the villages' awareness through scheduled interviews. The questions were categorized into five sections which are environmental awareness, water awareness, solid waste management, recycling awareness and demography. The finding shows that most of the respondents exhibited positive answers towards different awareness. Thirty households were interviewed in this study and the chi-square test was conducted to examine the significant difference between the independent variables with the dependent variables. Results indicate that there are significant differences between age, gender and education of the respondents.